2019
DOI: 10.35652/igjps.2019.92s24
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera- A Boom for Cancer Patients

Abstract: This is a special issue as an outcome of 'RAPSCON-2019' sponsored by APTI and organized by Sri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Studies have shown that Plant-derived compounds have been an important source of several clinically useful anti-cancer agents (Cragg and Newman, 2005;Yesil-Celiktas et al, 2010;Singh et al, 2011;Bronikowska et al, 2012). The findings also indicated that cytotoxic effect of…”
Section: Introductionmentioning
confidence: 93%
“…Studies have shown that Plant-derived compounds have been an important source of several clinically useful anti-cancer agents (Cragg and Newman, 2005;Yesil-Celiktas et al, 2010;Singh et al, 2011;Bronikowska et al, 2012). The findings also indicated that cytotoxic effect of…”
Section: Introductionmentioning
confidence: 93%
“…In Sanskrit, ashwagandha, the Indian name for Withania somnifera, means "odor of the horse", probably originating from the odor of its root which resembles that of a sweaty horse. The herb is termed as "Rasayana" in Ayurvedic practice, which means it acts as a tonic for vitality and longevity [6]. "Withania somnifera has been known for its potent antioxidant and free radical quenching properties in various conditions.…”
Section: World Health Organizationmentioning
confidence: 99%
“…According to Bhattacharya and Muruganandam [4], it possesses anti-stress qualities. Cytotoxic, antimicrobial, antifungal, immunosuppressive, and immunomodulatory qualities Singh [5]. As a sedative, for rheumatoid arthritis, for joint inflammation, for feminine diseases, for hiccups, against colds and coughs, for ulcers, as leprosy, etc.…”
Section: Introductionmentioning
confidence: 99%